Borna Disease Virus Persistence Causes Inhibition of Glutamate Uptake by Feline Primary Cortical Astrocytes - Billaud, Jean-Noel (American Society for Microbiology, 2000)
Borna disease virus (BDV), a nonsegmented, negative-stranded (NNS) RNA virus, causes central nervous system (CNS) disease in a broad range of vertebrate species, including felines. Both viral and host factors contribute to very diverse clinical and pathological manifestations associated with BDV infection. BDV persistence in the CNS can cause neurobehavioral and neurodevelopmental abnormalities in the absence of encephalitis. These BDV-induced CNS disturbances are associated with altered cytokine and neurotrophin expression, as well as cell damage that is very restricted to specific brain regions and neuronal subpopulations. BDV also targets astrocytes, resulting in the development of prominent astrocytosis. Astrocytes play essential roles in maintaining CNS homeostasis, and disruption of their normal activities can contribute to altered brain function. Therefore, we have examined the effect of BDV infection on the astrocyte's physiology. We present here evidence that BDV can establish a nonlytic chronic infection in primary cortical feline astrocytes that is associated with a severe impairment in the astrocytes' ability to uptake glutamate. In contrast, the astrocytes' ability to uptake glucose, as well as their protein synthesis, viability, and rate of proliferation, was not affected by BDV infection. These findings suggest that, in vivo, BDV could also affect an important astrocyte function required to prevent neuronal excitotoxicity. This, in turn, might contribute to the neuropathogenesis of BDV.